Microbial ecology - Barton, Larry 1940-; Northrup, Diana E. (Wiley-Blackwell, an imprint of John Wiley & Sons, 2011)
"Microbial Ecology presents a broad overview of microbial ecology while providing numerous special features to assist students, teachers, and the professional reader. Information boxes in each of the sixteen chapters highlight specific microbial ecology issues of particular interest. Included in the text, also, is a glossary and key words. The book covers a selected reading list for each chapter; a special section in each chapter on "microbial spotlights" that focus on the latest work and findings of scientists from around the world; and exercises that promote critical thinking. "--Provided by publisher.